2017
DOI: 10.1111/scs.12485
|View full text |Cite
|
Sign up to set email alerts
|

Residents' perceptions of the most positive and negative aspects of the housing situation for people with psychiatric disabilities

Abstract: The major aim of the present study was to explore what people with psychiatric disabilities, living in two different types of housing, consider to be the best and the worst in their housing situation. A secondary aim was to explore to what extent additional questions to a questionnaire with a free-response format can provide complementary information to the previous knowledge in the field. The content analysis revealed that the physical attributes were of great significance for the residents in ordinary housin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…It would thus appear that an adjustment to the PMA-H with the possible inclusion of OHS-specific items in a separate OHS-version is warranted in order to better suit that context. A similar conclusion was made in a study of satisfaction with housing and housing support for people with psychiatric disabilities (Brolin, Rask, Syren, Baigi, & Brunt, 2015; Brolin, Syrén, Rask, Sandgren, & Brunt, 2018). Major contrasts were found between the two housing forms in a number of aspects indicating the need for two different questionnaires to better suit the varying nature of the two contexts.…”
Section: Discussionsupporting
confidence: 77%
“…It would thus appear that an adjustment to the PMA-H with the possible inclusion of OHS-specific items in a separate OHS-version is warranted in order to better suit that context. A similar conclusion was made in a study of satisfaction with housing and housing support for people with psychiatric disabilities (Brolin, Rask, Syren, Baigi, & Brunt, 2015; Brolin, Syrén, Rask, Sandgren, & Brunt, 2018). Major contrasts were found between the two housing forms in a number of aspects indicating the need for two different questionnaires to better suit the varying nature of the two contexts.…”
Section: Discussionsupporting
confidence: 77%
“…Research has shown that staff attitudes towards recovery influence people with SMI’s level of participation, inhibiting their recovery ( Bitter et al, 2017 ; Linhorst et al, 2005 ; Macpherson et al, 2004 ; Pandiani et al, 1994 ) and likelihood of moving on to more independent living ( Killaspy et al, 2013 ; Killaspy et al, 2019 ). Other personal and environmental factors can affect an individual’s experience of personal empowerment including their illness experience, restrictions imposed by compulsory treatment orders and rules within SA which can restrict choices and involvement in decision making ( Brolin et al, 2018 ; Fossey et al, 2006 ; Nelson et al, 2001 ; Sandhu et al, 2017 ; Valdes-Stauber & Kilian, 2015 ). These environmental factors mean that staff have to uphold rules while also supporting individuals, limiting flexibility of approach which can hinder effective support for recovery ( Bengtsson-Tops et al, 2014 ; Coffey et al, 2019 ; Nelson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most activities reported in the diaries took place indoors, in the participant’s own apartment, and were carried out alone. This result is alarming as it has been shown in research that it is important for people with SMI to be in a social context, which can provide a positive identity [ 11 , 19 ], can increase the individual’s ability for self-determination [ 2 , 33 ] and can provide opportunities for individually chosen meaningful activities [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Krotofil, McPherson & Killaspy [3] pointed out that the residents' ability to make choices and exercise agency was contingent on the relationships between residents and staff and the ethos and principles behind the service provision. SH services that enable power-sharing between staff and residents and co-produced support and goal setting are warranted [2,5,33]. Furthermore, shared decision-making has been shown to be an important aspect of recovery-oriented services [44][45][46].…”
Section: Freedom Of Choice Goals and Power-sharingmentioning
confidence: 99%